Pemberdayaan Peternak Marginal: Studi Kasus di Wilayah Banguntapan Bantul - Irkham Widiyono; Sarmin Sarmin (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
Over the recent years, villagers in the countryside havefaced the problem of limited resources for livestock and crop productions. Decreased land quality and agricultural land areawith respect to the increased need for housing landhas resulted in economic and environmental problems for livestock farmers in this area. Most livestock farmers have poor standard of education, limited ownership of land and livestock, and  are not capable of managing the natural resources in sustainable ways. The present services for small livestock farmersare aimed to transform the unintegrated livestock and agricultural farming into  a sustainable integrated system in the marginal community. Some efforts were conducted to improve knowledge and skills in zero waste system in livestock and agricultural farming by livestock farmers in marginal areas. The present community development programs were conducted using farmer-centered learning methods (participative learning) and mentoring by professionals on the implementation of sustainable integrated farming system (learning by practice). Furthermore, institutional development and cooperative networking with related parties were carried out. Results showed that the livestock farmerswere able to adopt integrated farming practices and the community was capable of independently producing organic fertilizer from livestock wastes and converting agricultural byproducts into animal feed. Both farmers and villagers have come together to cultivate fruit and vegetable plantations in vacant lands and back yards which were previously unused. The farmers’ group has successfully networked with the related partners to ensure sustainability of environmental conservation efforts and improvement of livelihood. In conclusion, active participation of farmersin the marginal area throughout the development process and mentored-practice are key factors for successful agricultural transformation in the marginal community. Implementation of the sustainable integrated farming system will ensure food security, environmental protection and safety, conservation of natural resources, and better quality of life.